Meningkatkan Kemampuan Literasi Digital Siswa Melalui Pembelajaran Berbasis Teknologi - Azizah Adzra; Halimatus Sa'diah; Gusmaneli Gusmaneli (GLOBAL SCIENTS PUBLISHER, 2025)
Digital literacy is a crucial competency for students to navigate technology-based learning. This capability encompasses the skills to access, evaluate, manage, and create digital information critically, creatively, and responsibly. However, many students still face obstacles, such as weak ability to assess the credibility of information, unequal access to digital devices, low ethical standards in online activities, and limited teacher competence in utilizing technology pedagogically. The impact of weak digital literacy is evident in the emergence of misconceptions, underdeveloped critical thinking skills, declining learning outcomes, and reduced motivation for technology-based learning. To improve students' digital literacy, targeted strategies are needed, including the systematic integration of technology into learning, strengthening teacher skills through digital training, implementing project-based learning models involving technology, providing equitable digital facilities, and developing digital literacy programs within the school environment. These steps have the potential to create a more effective, interactive learning experience that is relevant to the needs of 21st-century competencies.